MTOR and other effector kinase signals that impact T cell function and activity. Issue 1 (12th August 2019) - Myers, Darienne R.; Wheeler, Benjamin; Roose, Jeroen P.
Abstract: T cells play important roles in autoimmune diseases and cancer. Following the cloning of the T cell receptor (TCR), the race was on to map signaling proteins that contributed to T cell activation downstream of the TCR as well as co‐stimulatory molecules such as CD28. We term this "canonical TCR signaling" here. More recently, it has been appreciated that T cells need to accommodate increased metabolic needs that stem from T cell activation in order to function properly. A central role herein has emerged for mechanistic/mammalian target of rapamycin (mTOR). In this review we briefly cover canonical TCR signaling to set the stage for discussion on mTOR signaling, mRNA translation, and metabolic adaptation in T cells. We also discuss the role of mTOR in follicular helper T cells, regulatory T cells, and other T cell subsets. Our lab recently uncovered that "tonic signals", which pass through proximal TCR signaling components, are robustly and selectively transduced to mTOR to promote baseline translation of various mRNA targets. We discuss insights on (tonic) mTOR signaling in the context of T cell function in autoimmune diseases such as lupus as well as in cancer immunotherapy through CAR‐T cell or checkpoint blockade approaches.